DEVELOPMENT OF INTERACTIVE MULTIMEDIA MODULES IN PROBLEM-BASED LEARNING MODELS TO ENHANCE CRITICAL THINKING ABILITIES OF HIGH SCHOOL STUDENTS - Shabrina Amalia; Djusmaini Djamas; Yulkifli Yulkifli (Universitas Negeri Medan, 2020)
Objective: to produce interactive multimedia modules in the Problem Based Learning (PBL) model to increase critical thinking skills that are valid, practical and effective. This type of research is R & D with a 4D models development model consisting of define, design, develop, and disseminate phases. At the define stage, a preliminary analysis, students, assignments, concepts, and formulation of learning objectives are carried out . The design phase is done by designing interactive multimedia modules in PBL models. The develop phase, validation by experts on interactive multimedia modules, and then carried out limited trials to see the practicality and effectiveness. Practical data is obtained from teacher and student questionnaires, then the effectiveness data is obtained from the achievement of knowledge, attitudes and skills competencies. The result of define phase is obtained information about the need to develop interactive multimedia modules in PBL models to increase critical thinking skills. The results of the design phase obtained the design of interactive multimedia modules referring to the needs analysis define phase. The results of module development meet valid criteria (0.88). Practical results according to teachers (96.4) and students (92.1). Thus it can be concluded that interactive multimedia modules are in a very practical category. Furthermore the effectiveness of the module on attitudinal competence (84.2), knowledge (81) and skills (71.9). The conclusion of this study is that interactive multimedia modules in the PBL model meet valid, practical and effective criteria